Management of Large Erupting Complex Odontoma in Maxilla - Colm Murphy; John Edward O’Connell; Edward Cotter; Gerard Kearns (Case Reports in Pediatrics)
We present the unusual case of a large complex odontoma erupting in the maxilla. Odontomas are benign developmental tumours of odontogenic origin. They are characterized by slow growth and nonaggressive behaviour. Complex odontomas, which erupt, are rare. They are usually asymptomatic and are identified on routine radiograph but may present with erosion into the oral cavity with subsequent cellulitis and facial asymmetry. This present paper describes the presentation and management of an erupting complex odontoma, occupying the maxillary sinus with extension to the infraorbital rim. We also discuss various surgical approaches used to access this anatomic area.